Ecological Impacts of Diesel Engine Emissions - Jurić, Vanja; Županović, Dino (Promet - Traffic&Transportation, 2012)
This article deals with the ecological impacts of chemical substances that are found in the structure of Diesel engine exhaust gases and provides an overview of legislation that limits their maximum allowable emissions. Special consideration is given to the previously mostly neglected negative impact of particulate matter compared to the impact of carbon dioxide. Negative impact of particulates is especially noted as direct negative impact on human health whereby the expenses associated with medical treatment exceed the financial savings resulting from the usage of Diesel powered vehicles. Therefore, the paper presents the knowledge acquired through previous scientific research in the economically most developed countries, as well as the tendencies for the reduction of negative impacts of Diesel exhaust gases.